Virtual reality games as a pain and anxiety reduction in circumcision children: A literature review - Suparda, Dadik Dwi Fata; Kurniawati, Ninuk Dian; Wahyudi, Andri Setiya (Universitas Airlangga, 2023)
Introduction: Circumcision is a minor surgical operation that cuts the foreskin at the tip of the penis. Pain and anxiety are problems that all children who undergo surgery experience. This study aimed to review virtual reality game interventions to reduce pain and anxiety from pre, intra, and post-circumcision in children.Methods: Literature study using four databases (Scopus, Science Direct, PubMed, and Google Scholar) using quantitative research with RCT and quasi-experimental designs, using virtual reality, audio-visual and game interventions which were limited from 2018 to 2022 according to combination of keywords and using English. The framework investigation using PICOT, guidance protocol with PRISMA, and accessing the eligibility of articles systematically by checking for duplicates, titles, and abstracts and determining the eligibility of the full text according to the study of the goals.Results: Thirteen articles met the inclusion criteria. Of the thirteen articles, 1074 children were circumcised. Circumcision causes pain and anxiety in children, so non-pharmacological interventions are needed to overcome it. Virtual reality games are a distraction technique to reduce circumcision pain by diverting the child's attention and reducing anxiety by providing interventions that children like using audio-visual media and games, with virtual reality or not.Conclusions: Virtual reality games intervention is a distraction technique to reduce pain and anxiety in circumcised children. The combination of interventions using traditional games or the latest technology must be considered to improve service quality. Keywords: anxiety; children; circumcision; distraction technique; pain